CARE-LEAVERS’ EXPERIENCES OF HOW MANAGED OPPORTUNITIES FOR INDEPENDENCE CONTRIBUTED TO BUILDING RESILIENCE - Hlungwani, Joyce; van Breda, Adrian D. (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2024)
Care-leaving literature widely utilizes resilience theory. This is due to an acknowledgment that while young people who grew up in care frequently achieve poorer outcomes during their transition from care to independent adulthood, some do well despite their challenges. Resilience research is also increasingly interested in the factors that promote resilient functioning during the transition out of care. However, research on how to build young people’s resilience while in care is limited. This paper introduces the notion of “managed opportunities for independence” (MOI), which are guided activities for young people that involve them acting independently. We explore the contribution of MOI in building the resilience of young people in care. Nine care-leavers who had disengaged from various residential care centers in South Africa were purposively sampled. The study employed a qualitative approach and a grounded theory design, with semi-structured individual interviews. Findings depict the range of MOI that care-leavers experienced, the ways in which these benefited them since leaving care, the kinds of independence they currently display as a result, and their suggestions for improving MOI. Implications for practice include proceduralizing MOI and making greater use of such opportunities to prepare young people for leaving care.